RNAi-mediated plant protection: Identification and characterization of the molecular components of the HIGS and SIGS pathways - Schlemmer, Timo; Justus Liebig University Giessen (My University, 2022)
RNA-based plant protection relies on the RNA interference (RNAi) mechanism responsible for gene silencing, regulation of transposable elements and viral defence. RNAi is evolutionarily conserved in eukaryotic organisms. At the beginning, double-stranded (ds)RNA is processed by Dicer enzymes into short interfering (si)RNAs. These, in turn, are incorporated into an RNA-induced silencing complex (RISC) with Argonaute (AGO) as the core component. AGO binds to siRNAs, separates the guide and follow strand and targets complementary transcripts, leading to the degradation of messenger (m)RNA, translational blocking or chromatin remodelling. dsRNA expressing transgenes as triggers of RNAi could be incorporated into hosts by modifying their genomes. These transgenes target essential genes of pathogenic origin and lead to resistance against fungi, nematodes, insects or viruses. If dsRNA is derived by transgenes RNAi-based silencing is termed host-induced gene silencing (HIGS) and relies on genetically modified organisms (GMOs). However, producing GMOs is a time-consuming and expensive process restricted to low numbers of varieties with existing transformation protocols. On the European market, GMOs are less accepted, so common foliar spray applications of dsRNA onto crops are more favourable. This approach is called spray-induced gene silencing (SIGS) and makes RNA-based pesticides applicable to a broader range of crops. A different origin of initiating dsRNA results in different participation of host or pathogenic RNAi machinery. While HIGS relies on plant-endogenous Dicers located in the nucleus, SIGS relies on Dicers of the target pests. Another difference is caused by unequal amounts of initiating dsRNA. The RNA delivered by SIGS approaches is limited to the RNA applied to leaf surfaces, as opposed to rather unlimited amounts of dsRNA expressed by a host’s transgene. Therefore, RNA stability and uptake into leaves are from special interest in SIGS approaches. Several formulations enhancing solutions’ wetting capacity possibly allows stomatal flooding to occur in line with stomatal RNA uptake into leaf tissue. Finally, uptake into plant cells by endocytosis is speculated upon. However, if RNA is derived transgenically or by spray application, systemic spreading of RNA through plant tissue by vascular tissue has been shown in previous research and leads to systemic protection in unsprayed plant parts. Lastly, RNAi-associated factors must cross the borders between plant cell and pathogenic (i.e. fungal) cells. For Fusarium graminearum, CYP3RNA-dependant resistance was observed in HIGS and SIGS approaches, but translocation of CYP3RNA-associated factors between plant and Fusarium graminearum is still unclear. Extracellular vesicles (EVs), which are spherical lipid compartments, are released into the apoplast by plant cells and are possible transport vehicles of RNAi-mediating factors. EVs are known to contain a broad variety of nucleic acids, proteins and lipids specific to their source. To test EV dependency in CYP3RNA-mediated resistance, EVs were purified from CYP3RNA-expressing Arabidopsis thaliana plants or CYP3RNA-sprayed barley leaves. An EV isolation protocol from Arabidopsis plants has already been published. Isolation protocols to study barley or Fusarium graminearum EVs were developed (see section D: Elucidating the role of extracellular vesicles in the Barley-Fusarium interaction). Effects of fungal EVs on plants include host-specific lesions on barley but not in the non-host plant Nicotiana benthamiana after the infiltration of EVs into leaves. Purified EVs of barley result after drop inoculation onto Fusarium graminearum plates in fungal colony discolouration visualising fungal stress reaction to plant EVs or content. Further characterization of barley EV content revealed CYP3RNA-derived small RNAs, indicating CYP3RNA transport between plant host and fungal recipient cell (see section E: Isolation and characterization of barley (Hordeum vulgare) extracellular vesicles to assess their role in RNA spray-based crop protection). Co-cultivation studies of plant-derived EVs from either CYP3RNA-expressing Arabidopsis plants or CYP3RNA-sprayed barley leaves in liquid phase have revealed no effect of plant EVs or associated CYP3RNAs on fungal growth (see section F: Extracellular vesicles isolated from dsRNA-sprayed barley plants exhibit no growth inhibition or gene silencing in Fusarium graminearum). It is questionable whether an improper uptake of EVs or low number of either EVs or CYP3RNA-derived small RNAs are responsible for the lack of target gene silencing, leaving the responsibility of plant EVs in HIGS- or SIGS-mediated plant protection unclear.
Keywords: RNAi; plant protection; barley; HIGS; SIGS; Fusarium; RNA-based plant protection; EV; extracellular vesicles; ddc:500